2013
DOI: 10.5551/jat.14365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lutein Supplement on Serum Inflammatory Cytokines, ApoE and Lipid Profiles in Early Atherosclerosis Population

Abstract: Aim:The purpose of this study was to determine the effects of lutein supplement on serum cytokines, apoE and lipoprotein profiles in early atherosclerosis population. Methods: Early atherosclerosis patients (n = 65) were randomized to receive placebo (A+P, n = 31) or 20 mg/d lutein (A+L, n = 34) for 3 months. Results: Serum lutein increased significantly compared to baseline after lutein supplements in A+L group (p<0.001). Lutein supplements resulted in a significant decrease in serum interleukin-6 (IL-6) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…Lutein is one of spontaneously generating carotenoids with anti-oxidative, anti-tumorigenic, anti-angiogenic, photoprotective, hepatoprotective, and neuroprotective properties [1619]. Although the anti-inflammatory property of lutein has been suggested, the mechanism of lutein-mediated anti-inflammatory action in various skin inflammatory responses remains largely unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutein is one of spontaneously generating carotenoids with anti-oxidative, anti-tumorigenic, anti-angiogenic, photoprotective, hepatoprotective, and neuroprotective properties [1619]. Although the anti-inflammatory property of lutein has been suggested, the mechanism of lutein-mediated anti-inflammatory action in various skin inflammatory responses remains largely unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Lutein (Figure 1) is one of naturally occurring carotenoids with antioxidative, antitumorigenic, antiangiogenic, photoprotective, hepatoprotective, and neuroprotective properties [1619]. Previous reports have suggested that this compound is able to ameliorate in vitro and in vivo inflammatory responses by suppressing NF- κ B activation [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence from animal studies suggests that lutein prevents cholesterol accumulation in aortic tissue in atherosclerotic guinea pigs [27]. Epidemiological data support the finding that an increase in serum lutein after supplementation reduces the serum levels of low density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) [28]. Furthermore, progression of the intima-media thickness (IMT) of the common carotid arteries over 18 months was related to plasma lutein levels among a randomly sampled cohort of utility employees aged 40-60 years [29].…”
Section: Introductionmentioning
confidence: 87%
“…Given the beneficial antioxidant and antiinflammatory properties [16], it is hypothesized that lutein may have beneficial effects on inflammatory biomarkers and metabolic risk factors. Xu et al [17] provided early atherosclerosis patients with lutein supplementation and found that the intervention group had a significant decrease in serum IL-6 and MCP-1. Another intervention study conducted in healthy nonsmokers revealed that lutein supplementation increased total antioxidant capacity and reduced CRP [18].…”
Section: Introductionmentioning
confidence: 99%